Minimum support price in India: what determines farmers’ access? - Raya Das (Agricultural Economics Research Review, 2023)
The paper evaluates the access of farmers to Minimum Support Price (MSP) for paddy and wheat across farm size groups and states based on a large-scale farm survey conducted in 2012-13. We have assessed the efficiency of MSP policy by estimating the percentage of farmers selling paddy and wheat to Public Procurement Agencies (PPAs), the price they sold at, and the quantity of the crop sold at that price. The north-eastern states have the least access to MSP followed by the eastern states. The odds of selling to PPAs are low among small farmers, and the socially-disadvantaged households.